2023
DOI: 10.1039/d3tc00415e
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Brønsted acidic dopants in conjugated polymers

Abstract: An examination of the mechanism of electrical doping of films of poly(3-hexylthiophene) by a strong Brønsted acids reveals a heavily doped surface layer that limits diffusion of the acid into the bulk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…For example, fuel cells require H + conduction, while batteries rely on metal cation conduction. Anion transport can also be of interest, where semiconducting applications typically focus on mixed conduction in the context of dopant counterion diffusion . For the next generation of mixed conducting polymers, structure–property relationships must be developed to enable predictable tunability of a range of transport properties for these highly tailored applications .…”
Section: Introductionmentioning
confidence: 99%
“…For example, fuel cells require H + conduction, while batteries rely on metal cation conduction. Anion transport can also be of interest, where semiconducting applications typically focus on mixed conduction in the context of dopant counterion diffusion . For the next generation of mixed conducting polymers, structure–property relationships must be developed to enable predictable tunability of a range of transport properties for these highly tailored applications .…”
Section: Introductionmentioning
confidence: 99%
“…Previously, study showed that TFSI − counterion has very restricted diffusion above the observed doping depth even with prolonged thermal annealing at elevated temperature. 18 This could be ascribed to the increased modulus and shift in T g observed for doped conjugated polymers, and thus limiting the mobility of the counterions from the doped surfaces. 48,49…”
Section: Resultsmentioning
confidence: 99%
“…Recently, our group has reported the kinetics of doping and diffusion of Brønsted acid doping from solution of P3HT using HTFSI. 18 The coupled P3HT + :TFSI À pairs showed a relatively slow diffusion coefficient of B1.0 nm 2 min À1 based on reaction-diffusion modeling. Although methanol was used as the solvent for the acid doping process, which swells P3HT differently than DCM, we can use the diffusion coefficient as a rough estimate here.…”
Section: Solvent Controls the Doping Depth Of P3htmentioning
confidence: 98%
See 2 more Smart Citations